Competent to manage - Silver, Mick (M. S.), 1951- (London ; New York : Routledge, 1991)
This book is divided into three parts: The context: a crisis in management training in the UK; What education and training do our managers need?: performance and competence; and What is to be done?
Keywords: Management; Executives; Executives -- Training of -- Great Britain; Management -- Study and teaching -- Great Britain